Assessment of Sarcopenia Related Quality of Life Using SarQoL® Questionnaire in Patients With Liver Cirrhosis - Iacob, Speranta; Mina, Victor; Mandea, Matei; Iacob, Razvan; Vadan, Roxana; Boar, Voichita; Ionescu, Georgeta; Buzescu, Dan; Gheorghe, Cristian; Gheorghe, Liana (Frontiers in Nutrition, 2022)
Introduction Sarcopenia, malnutrition, physical deconditioning, and frailty contribute to a significantly altered quality of life (QoL) in patients with cirrhosis and sarcopenia. Aim To investigate the sarcopenia-linked alterations of QoL by SarQoL® questionnaire in patients with end-stage liver disease. Methods Consecutive patients with liver cirrhosis, admitted to our department between May and August 2021, completed the SarQoL® questionnaire by themselves. They were evaluated for sarcopenia according to the 2019 European Working Group on Sarcopenia in Older People (EWGSOP) definition [hand grip cut-offs and skeletal muscle index (SMI) calculation at CT scan]. Results A total of 71 patients with liver cirrhosis were included in the study, with a median age of 54 years. Sarcopenia was present in 31.2% of patients with Child-Pugh class A, in 58.3% with class B, and in 93.5% with class C. The SarQoL® score was statistically significant and lower in Child-Pugh class C vs. class B and class A (70.2 vs. 66.5 vs. 52.5 points, p = 0.0002). The SarQoL® score was evaluated according to different complications of cirrhosis, with statistically significant lower scores in patients with sarcopenia (p < 0.0001), in patients with ascites requiring paracentesis (p = 0.0006), and in patients with hepatic encephalopathy (p < 0.0001). A cut-off level of 75.9 points for SarQoL® score can accurately detect sarcopenia in patients with end-stage liver disease [area under the receiver operating characteristic (AUROC) curve of.823, SE of 92.1%, SP of 45.5%, positive predictive value (PPV) and negative predictive value (NPV) of 66 and 83.3%, respectively, correctly classified 73.2% of cirrhotic patients with sarcopenia]. Conclusions The use of SarQoL® questionnaire in cirrhotic patients can, at the same time, evaluate the quality of life and identify subjects with sarcopenia and altered QoL.